Impact of plasma discharge pressure on implant surface properties and osteoblast activities in vacuum-assisted plasma treatment - Ara Jung; Hyungyu Lee; Heejin Kim; Hyun Jeong Jeon; Sanghoo Park; Bomi Gweon (Scientific Reports)
Abstract Nonthermal plasma has been extensively utilized in various biomedical fields, including surface engineering of medical implants to enhance their biocompatibility and osseointegration. To ensure robustness and cost effectiveness for commercial viability, stable and effective plasma is required, which can be achieved by reducing gas pressure in a controlled volume. Here, we explored the impact of reduced gas pressure on plasma properties, surface characteristics of plasma-treated implants, and subsequent biological outcomes. Implant materials were treated with plasmas under varying discharge conditions, with pre-pumping times of 10 s and 20 s, thereby modulating the pressure during plasma treatments. Through optical emission spectroscopy, we demonstrated that the 5 Torr operational condition, achieved by 20-s pre-pumping, generated a greater density of excited nitrogen species and provided more stable plasma compared to the 16 Torr condition, achieved by 10-s pre-pumping. We then assessed the surface hydrophilicity, chemical composition, protein adsorption, and osteoblast activities on plasma-treated implants compared with those of untreated controls. Our results reveal that the 5 Torr condition significantly enhances removal of carbon-based impurities and increased protein adsorption, leading to improved cell adhesion, proliferation, and differentiation. In particular, implants treated under the 5 Torr condition showed significantly higher carbon-based impurity reduction and osteoblast differentiation performance compared to those treated under the 16 Torr condition. These findings suggest that optimizing gas pressure in plasma devices is critical for effectively controlling excited nitrogen radicals, which improves plasma surface modification and enhances the biocompatibility of implant surfaces.